Reconciliation of professional and private life : exchange of good practices (Office for Official Publications of the European Communities, 2007)
Striking the right balance between work and home lives also enables people to take control of when and how they work. This balance can only be achieved once it is accepted and respected as a right that benefi ts individuals, businesses and society as a whole. Demographic studies highlight that reconciliation is set to become an increasingly important issue, with greater numbers of women entering the workforce and an increasingly large ageing population. In order to ensure that workers can exercise their right to balance their personal and professional lives, it will be necessary to break down the barriers that exist on two levels. Firstly, employers should be made aware that reconciliation measures could result in increased productivity, lower rates of absenteeism and a more satisfied and productive workforce. Secondly, men and women will need to overcome traditional gender stereotypes about their roles in and beyond the home.